Modeling and Design of Induction Heating Systems - Mendi Altube, Amaiur; Villar Iturbe, Irma; Carretero Chamarro, Claudio; Acero Acero, Jesús (Jornada de Jóvenes Investigadores del I3A, 2024)
This thesis is based on a specific industrial application of induction heating technology: induction hardening. The main objective is to create a simulation model that predicts the whole heating process, combining the electrical simulation with the electromagnetic-thermal analysis, employing electrical simulation software and finite element tools, respectively. This proposed model will be called as dynamic model in the following lines.